ÉTUDE ETHNOBOTANIQUE ET ÉVALUATION IN VITRO DE L’ACTIVITE ANTIFONGIQUE DES EXTRAITS DE FEUILLES DE Mallotus oppositifolius SUR DEUX SOUCHES PHYTOPATHOGENES DE Sclerotium rolfsii - Bernadine, Orsot Bosson Arobia Marie; Sibirina, Soro; Djakalia, Ouattara; Kouakou, N’guessan Edouard; Noël, Zirihi Guédé (European Scientific Journal, ESJ, 2015)
The study was conducted to know the medicinal plants used to treat fungal skin diseases in the department of Agboville in Côte d'Ivoire. An ethnobotanical study conducted in this department permitted to identify 26 species of medicinal plants used in the treatment of skin diseases. Mallotus oppositifolius (Euphorbiaceae), species most used, was employed for testing in vitro, by using double dilution method on PDA medium, the sensitivity of two fungal strains Sclerotium rolfsii. MIC and MFC of the gowth of spawn were obtained at 100 mg/ml and 200 mg/ml for the aqueous extract and 12,5 mg/ml and 25 mg/ml for ethanol extract. The MIC of the sclerotia’s germination was 6,25 mg/ml and the MFC was 12,5 mg/ml for the two strains. This inventory is a way of safeguard of the population’s knowledge which is disappearing. This study can be considered as a basic work for in vivo biological struggle against Sclerotium rolfsii.